2017
DOI: 10.1007/s11046-017-0180-2
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Candiduria and Candidemia: A Clinical and Molecular Analysis of Cases

Abstract: The risk of developing candidemia after candiduria is reportedly very low, but it has not been adequately investigated. The aim of this study was to examine the molecular relatedness between Candida strains isolated from adult patients with candidemia and concomitant candiduria in association with the clinical characteristics of the cases. All episodes of candidemia occurring in a tertiary care academic hospital during a 5-year period were recorded prospectively. Patients with episodes of candiduria occurring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…However, candiduria is rarely clinically significant. Drogari-Apiranthitou et al 11 conducted a 5-year clinical and molecular analysis of cases with candidemia and candiduria and found that concomitant candiduria is rare in hospitalized patients with candidemia, confirming previous reports. Hence, the 2015 NHSN definition change has likely led to a more appropriate attribution of catheter-related candidemia by excluding CAUTI as a potential source.…”
Section: Discussionsupporting
confidence: 69%
“…However, candiduria is rarely clinically significant. Drogari-Apiranthitou et al 11 conducted a 5-year clinical and molecular analysis of cases with candidemia and candiduria and found that concomitant candiduria is rare in hospitalized patients with candidemia, confirming previous reports. Hence, the 2015 NHSN definition change has likely led to a more appropriate attribution of catheter-related candidemia by excluding CAUTI as a potential source.…”
Section: Discussionsupporting
confidence: 69%
“…While candiduria is highly prevalent in hospitalised patients, the presence of concomitant candidaemia is infrequently encountered. 1,4 Our study revealed that out of the 4240 patients with candiduria, only 263 cases (6.2%) had concomitant candidaemia.…”
Section: Discussionmentioning
confidence: 66%
“…Candiduria is a frequent finding amongst hospitalised patients with a global incidence rate of 27.4 per 1000 patient admissions . The presence of yeast in the urine commonly represents benign colonisation of the urinary tract or perineum, but can also be a sentinel of a haematogenous infection .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies in experimental animals and clinical observations have indicated that the kidney consistently acts as the main fungus-bearing organ during candida infection [3][4][5]. In severely ill patients, candiduria has been considered to be significantly associated with disseminated candidiasis [6][7][8]. In surgical intensive care unit (ICU) settings, candiduria has been proved to be an independent factor associated with mortality [9].…”
Section: Introductionmentioning
confidence: 99%